Mutual Standby Power Supply System for SS7C Electric Locomotive - TANG Quanhai (机车电传动)
To improve the reliability of locomotive DC 600 V train power supply system, the scheme of adding one 400 kW power supply circuit based on the existed two power supply circuit for backup was presented, as well as adding a inverter cabinet for backup of the phase splitter, which was validated improved the reliability of the train power supply system greatly by operation test.